Redesigning courses for online delivery design, interaction, media & evaluation - Parker, Robyn E. (Emerald, 2013)
This volume examines key considerations for effective online course redesign. Using a 4-phase approach, Redesigning Courses for Online Delivery informs thinking, inspires creativity, and structures decisions to drive the development of high quality online learning experiences. Both scholarly and practical, it provides a comprehensive approach to redesign useful to novices and veterans alike.
Keywords: Education -- Computers & Technology.; Education -- Higher.; Education -- General.; Educational equipment & technology, computer-aided learning (CAL); Colleges of higher education.; Education, Higher -- Computer-assisted instruction.; Web-based instruction.; Instructional systems -- Design.; Educational technology.; elektronické knihy; electronic books